ظواهر تعليم اللغة العربية وعملية تفعيل المجال التعليمي - Fauziah, Fauziah (UIN Maulana Malik Ibrahim Malang, 2021)
This article aims to describe the phenomena in learning Arabic in relation to the problems faced by learning Arabic and how to make the learning process more effective. The approach used in this study is a qualitative approach with the type of literature study research in which data and data sources are obtained through notes and studies of some literature related to the main theme.The results of this study are that in general, the phenomenon of learning Arabic is the difference in letter patterns, morphemes and structures that affect the adaptation of learners in applying them in maharah lughawiyyah learning. Therefore, problems are often experienced, especially in the process of transforming information through maharah istiqbaliyah and its expression through productive maharah. Thus, it is important for Arabic teachers to pay attention to this issue to improve the quality of learning Arabic.